Prospective comparison of liver stiffness measurement methods in surveillance biopsies after liver transplantation - Bosselmann, Emily A.; Engel, Bastian; Hartleben, Björn; Wedemeyer, Heiner; Jaeckel, Elmar; Maasoumy, Benjamin; Potthoff, Andrej; Zender, Steffen; Taubert, Richard (Frontiers in Transplantation, 2023)
Background: Liver stiffness measurements (LSMs) have proven useful for non-invasive detection of fibrosis. Previous studies of LSMs after transplantation were performed in cohorts dominated by hepatitis C reinfections and indication biopsies for the evaluation of graft dysfunction. However, the diagnostic fidelity of LSMs for fibrosis is biased by inflammation e.g., during replicative hepatitis C or rejection. Materials and Methods: The current study aimed for a head-to-head comparison of two different LSMs, acoustic radiation force impulse (ARFI) and transient elastography (TE), and a determination of cut-off values for the detection of advanced fibrosis (any LAF score component ≥2) in grafts undergoing surveillance biopsies (svLbx) without recurrent hepatitis C. Results: 103 svLbx were paired with valid LSMs at time of biopsy. AUROC analyses showed significant positive correlation with fibrosis for both methods (TE: AUROC=0.819 (p<0.001; 95%CI: 0.717–0.921); ARFI: AUROC=0.771 (p=0.001; 95%CI: 0.652–0.890). Patients were randomly assigned to training and validation cohorts for both LSM methods. Cut-off values were determined at 1.29m/s (ARFI) and at 7.5kPa (TE) in training cohorts. Sensitivity and specificity in training and validation cohorts were: TE: SEN 0.818 and 0.5; SPE 0.742 and 0.885; ARFI: SEN 0.818 and 1.0; SPE 0.75 and 0.586. LSMs were not associated with BANFF criteria for relevant graft injury. Conclusion: LSM is a good non-invasive tool to screen for advanced graft fibrosis but not for relevant graft injury in patients with (near) normal liver enzymes. Fibrosis cut-off values identified and validated in svLbx were lower than in previous cohorts using indication biopsies.